Pathways to the Geosciences Summer High School Program: A Ten-Year Evaluation. Issue 1 (15th February 2016) - Carrick, Tina L.; Miller, Kate C.; Hagedorn, Eric A.; Smith-Konter, Bridget R.; Velasco, Aaron A.
ABSTRACT: The high demand for scientists and engineers in the workforce means that there is a continuing need for more strategies to increase student completion in science, technology, engineering, and mathematics (STEM) majors. The challenge lies in finding and enacting effective strategies to increase students' completion of STEM degrees and in recruiting students to these disciplines, especially those from underrepresented minority groups. This article presents results from 10 years of data from collected during a 2-week summer program for high school students in geosciences targeted at participants of Hispanic American origin in El Paso, Texas. The short-term goal of the program was to introduce the students to the geosciences and to inform them of the possibilities of the geosciences as a college major and career choice. The long-term goal was to form a pipeline from the summer program to undergraduate and graduate programs at the University of Texas at El Paso. Short-term indicators show statistically significant positive changes in student attitudes towards science and the geosciences over the course of the program. Long-term indicators show that 55% of the participants entered STEM majors in college and that 20% either are or were geoscience majors in college. By comparison, nationally only 9% of geoscience bachelor's degree graduates are from underrepresented minorities. These results suggests that summer high school programs in the geosciences can have a significant impact on increasing the number of underrepresented minority students who choose the geosciences for a career.